Otentisitas al-Qur’an: Bantahan Pandangan Abraham Geiger terhadap Al-Qur’an - Pertiwi, Lola; Rahman, Taufik; Syachrofi, Muhammad (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2023)
Abraham Geiger stated that the Qur'an took a lot from the teachings of the Jewish religion, both cultural and transcendent. This study aims to discuss and refute the views of an orientalist named Abraham Geiger on the authenticity of the Qur'an. This study uses a qualitative method with a literature study approach. The results and discussion of this study indicate that Abraham Geiger's accusation that the Koran is only a reflection of Muhammad on Judaism and Christianity is a false accusation. The accusations made by Abraham Geiger do not eliminate the authenticity of the Qur'an as the holy book of Muslims, because historical facts prove that the entire contents of the Qur'an were narrated by many people who continued the chain to the Messenger of Allah. If the criteria for news of mutawatir are mentioned, then the Qur'an has met that criterion.